INTEGRATED REPORTING QUALITY AND FIRM PERFORMANCE: EVIDENCE IN ASIA - Yane Devi Anna, (ADVANCED INTERNATIONAL JOURNAL OF BANKING, ACCOUNTING AND FINANCE (AIJBAF), 2024)
The objective of this study is to find out how the development of Integrated Reporting Quality is still voluntary in most countries and how it affects firm performance. The research was conducted on companies that have included the title "Integrated Reporting," while the data was obtained on the International Integrated Reporting Council website for the period 2020-2022. The method of data analysis through content analysis is employed to verify that the components and sub-components are truly essential elements of integrated reporting, as outlined in the integration reporting framework established by the IIRC. Processing research data using regression. The research results show that Integrated Reporting Quality affects company performance. Integrated reporting provides a complete picture of company activities and can help companies expand their investor base, resulting in lower capital costs.